Magnetization dynamics in magnetic media (Publicaciones en Ciencias y Tecnología, 2015)
This work is a study of magnetization evolution in magnetic media along the time. The magnetic media is a flat tape, like a tape use for record and tape information, with effective field including first order term from cubic net, uniaxial anisotropics fields, demagnetized field and interchange term between the net elements. The magnetization is driven from the demagnetized to the magnetized state by a dc applied magnetic fiel.The theoretical model show a solution of a Landau-Lifshitz-Gilbert equation, taking into account the speed of the tape. Four physicaly admisible solution are obtained: harmonic oscillations, damped oscillation, exponential fronts and double exponential fronts, for a different parameter values. We show an approximation to the problem from the dynamical system theory, when the equation is converted into a non-time depending autonomous system, for study the existence of fix points, the transition between solutions and the phase map of the solutions and his physical interpretation. The different phase map are presented for representative sets of values. This approximation to the problem complements and enriches the previous works.
Keywords: Dynamical systems; fase map; magnetization; magnetic media